PO.2.37 Risk factors for recurrent thrombosis and cause of death in patients with antiphospholipid syndrome; a Swedish cohort study. (27th September 2022) - Karandyszowska, N; Alagündüz, H; Oesman, J; Magnusson, M; Svenungsson, E; Bruzelius, M; Antovic, A
Abstract : Background: In patients with the antiphospholipid syndrome (APS), recurrent thrombosis (re-thrombosis) is common despite anticoagulation and the mortality rate is high. Concomitant systemic autoimmune rheumatic diseases (SARD) are frequent in patients with APS and often associated with disease associated damage. Less is known about the prevalence of non-rheumatic autoimmune diseases (NRAID) in these patients. Purpose: To estimate the incidence of re-thrombosis and death, evaluate the impact of cardiovascular (CV) risk factors and antiphospholipid antibody (aPL) profiles on re-thrombosis and identify causes of death in a novel APS cohort. To evaluate the incidence and prevalence of concomitant autoimmune diseases (AID) in this cohort. Methods: This retrospective cohort study comprises all patients identified with APS in the electronic medical records at Karolinska University Hospital, Sweden 2014–2020. Descriptive statistics was presented as median and interquartile range (IQR). Cox proportional hazards regression analyses were used to investigate the effect of risk factors. Results: 271 patients were included in the cohort. Age of APS-diagnosis was 43 years (IQR 31–55) and 66% were women. At inclusion, 130 (48%) patients presented with AID; 101 (37%) had a concomitant SARD while 54 (19%) had a NRAID. Systemic lupus erythematosus was the most frequent in 30%, followed by autoimmune thyroid disease in 10% of patients. During follow-up, 37 re-thrombosis occurred; 23 arterial and 14 venous events, with an incidence of 3.4 per 100 person-years (95% CI: 2.4–4.7). Significant CV risk factors for re-thrombosis were current smoking; hazard ratio 2.50, p=0.03 and chronic kidney disease; 3.44, p <0.01. Twenty-seven (73%) patients with re-thrombosis were triple positive for aPL compared to 113 (48%) without any event at follow-up (p <0.01). The cumulative death incidence was 4% (n=12) with sepsis due to bacterial infection being the most common cause. The median age at death was 63 years (IQR 51–71) and occurred 8 years (IQR 2–10) after diagnosis. In addition, 35 (13%) APS-patients developed AID during the study period, corresponding to an incidence rate of 28.4 (95% CI; 19.3–40.3) per 1.000 person-years with mean time at risk of 4 (SD±2) years. Conclusion: APS patients are at high risk to develop other AID during the 5 years follow-up period. Multiple CV risk factors are present in APS-patients suffering re-thrombosis, with smoking and chronic kidney disease being most important. APS-patients are susceptible to sepsis following bacterial infection with high mortality. These findings might be helpful when considering risk stratification and alternate treatment options in this patient group.